Image from post-photography: A conceptual review - Olivio, Alejandra; Lau, Jesús; Herrera, Edith (Arte, Individuo y Sociedad, 2023)
Photography and post-photography have historically been the subject of debate and criticism. The emergence of post-photography modified the conception of the photographic image based on its intrinsic relationship with digital technological advances, as recent literature has shown. In a mediatized society, with an abundance of information and immersed in visual content, analyzing the concept of post-photography helps to understand the processes of representation and communication through which a new generation. Concepts often condition the way in which subjects relate to their reality, so, in this document, the definition of post-photography is approached based on a chronological conceptual bibliographic review, from its emergence in 1988 with the main authors who contributed to the development of the concept, to its appropriations in the context of the contemporary media landscape. As a result, it can be observed that the evolution of post-photography has been marked by diverse positions throughout more than three decades of discussion, in which the ontological character of photography is blurred within the framework of digital media. The post-photographic image finds new niches of representation, communication and socialization, which transcend the scope once conferred to photography.